HANDBOOK OF POLITICAL SCIENCE - Polsby, Nelson W. (autor); Greenstein, Fred I (edición) (1975)
CONTENIDO: V.1. POLITICAL SCIENCE : SCOPE AND THEORY. -- V.2. MICROPOLITICAL THEORY. -- V.3. MACROPOLITICAL THEORY. -- V.4. NONGOVERNMENTAL POLITICS. -- V.5. GOBERNMENTAL INSTITUTIONS AND PROCESSES. -- V.6. POLICIES AND POLICYMAKING. -- V.7. STRATEGIES OF INQUIRY. -- V.8. INTERNATIONAL POLITICS